2016
DOI: 10.1177/2041386615584009
|View full text |Cite
|
Sign up to set email alerts
|

Identity and identification at work

Abstract: Work identity and identification have generated a great deal of interest in the fields of organizational psychology and organizational behavior. Given several theoretical perspectives available to study work identity, the field has developed in somewhat haphazard fashion with independent streams of research investigating the same or highly similar phenomena. In the present review, we provide a broad overview of theoretical approaches and topics in work identity literature to inform and guide future integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
197
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(208 citation statements)
references
References 201 publications
(228 reference statements)
3
197
1
7
Order By: Relevance
“…This study also suggests at least two possible additions to social identity theory as it applies to work settings. (1) Although organizational identification has mostly been studied as a unidimensional concept (Miscenko & Day, 2016), this study supports the notion that employees identify with at least two organizational foci (workgroup and organization), which is in line with findings on multiple foci of identification (Ashforth & Johnson, 2001;George & Chattopadhyay, 2005). (2) The study also shows that employees seem to identify less strongly with their organizations than with their workgroups, which supports previous findings that proximal targets are likely to achieve relatively more identification (Van Knippenberg & van Schie, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also suggests at least two possible additions to social identity theory as it applies to work settings. (1) Although organizational identification has mostly been studied as a unidimensional concept (Miscenko & Day, 2016), this study supports the notion that employees identify with at least two organizational foci (workgroup and organization), which is in line with findings on multiple foci of identification (Ashforth & Johnson, 2001;George & Chattopadhyay, 2005). (2) The study also shows that employees seem to identify less strongly with their organizations than with their workgroups, which supports previous findings that proximal targets are likely to achieve relatively more identification (Van Knippenberg & van Schie, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In their study on work identification, Miscenko and Day (2016) concluded that the most acknowledged approach to social identification with organizations is Mael and Ashforth's (1992) approach, which defines organizational identification as 'the perception of oneness with or belongingness to an organization, where the individual defines him or herself in terms of the organization(s) of which he or she is a member' (Mael & Ashforth, 1992, p. 104). This definition takes a strictly cognitive position based on social identity theory and self-categorization theory.…”
Section: Social Identification As a Potential Mediator Between Job Rementioning
confidence: 99%
“…A person's profession represents much more than their aptitudes and functions; it is a form of life to be assumed, as the relation between the workers and their profession is characterized by the engagement and by the feeling of identity and compliance with its attributes. The professional identity, therefore, plays a vital role in how individuals give meaning to our work environment and manage their careers; it is an important input for the construction of work identity (Dubar, 2015;Hay, 2014;Miscenko & Day, 2016).…”
Section: Analysis Of the Professions Under The Students' Eyes: A Possmentioning
confidence: 99%
“…Social identity theory was established in social psychology, branching from the developmental psychology tradition (Hammack, 2008) and has been a part of the expansion of identity research for at least 20 years (Ashforth, 2016;Jenkins, 2008;Miscenko & Day, 2016). "Although originally an analysis mainly of intergroup relations between large-scale categories," current research utilizes "a strong social cognitive emphasis" (Hogg, Abrams, Otten, & Hinkle, 2004, p. 246).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These identities form prototypes or schema that contain the attributes that distinguish groups from each other, providing similarities and differences for comparison (Hogg & Reid, 2006;Miscenko & Day, 2016). These schema do not simply label others, they are also used for self-identification.…”
Section: Theoretical Frameworkmentioning
confidence: 99%